Understanding Hyperemesis Gravidarum, Urinary Tract Infection, and Total Placenta Previa: Threats in Early Pregnancy - Gultom, Abitmer; Rombe, Claudia Valoryn Iona; Tanggo, Christian Ronald (Rifa'Institute, 2025)
Introduction: Hyperemesis gravidarum is a condition of excessive vomiting during pregnancy, occurring before 20 weeks of gestation. Urinary tract infections (UTIs) involve infections affecting any part of the urinary tract, and pregnant patients are more susceptible to UTIs. Placenta previa is a condition where the placenta partially or completely covers the internal cervical os. These three conditions have significant impacts on maternal and fetal well-being, necessitating a thorough understanding of their pathophysiology, diagnosis, and appropriate management. Objective: To report a case of hyperemesis gravidarum, urinary tract infection, and total placenta previa in a 30-year-old female patient. Case Report: A 30-year-old G2P1A0 woman presented with complaints of vomiting more than 8 times per day and brownish spotting, later diagnosed with hyperemesis gravidarum, UTI, and total placenta previa. Result and Discission: Findings included ketonuria, bacteriuria, bleeding from a closed external cervical os, and ultrasound imaging showing the placenta covering the internal cervical os. Conclusion: The patient was hospitalized and received appropriate medical management.